Editor's Highlight: Multiparametric Image Analysis of Rat Dorsal Root Ganglion Cultures to Evaluate Peripheral Neuropathy-Inducing Chemotherapeutics. (23rd January 2017) - Guo, Liang; Hamre, John; Eldridge, Sandy; Behrsing, Holger P.; Cutuli, Facundo M.; Mussio, Jodie; Davis, Myrtle
Abstract : Chemotherapy-induced peripheral neuropathy (CIPN) is a major, dose-limiting adverse effect experienced by cancer patients. Advancements in mechanism-based risk mitigation and effective treatments for CIPN can be aided by suitable in vitro assays. To this end, we developed a multiparametric morphology-centered rat dorsal root ganglion (DRG) assay. Morphologic alterations in subcellular structures of neurons and non-neurons were analyzed with an automated microscopy system. Stains for NeuN (a neuron-specific nuclear protein) and Tuj-1 (β-III tubulin) were used to identify neuronal cell nuclei and neuronal cell bodies/neurites, respectively. Vimentin staining (a component of Schwann cell intermediate filaments) was used to label non-neuronal supporting cells. Nuclei that stained with DAPI, but lacked NeuN represented non-neuronal cells. Images were analyzed following 24 h of continuous exposure to CIPN-inducing agents and 72 h after drug removal to provide a dynamic measure of recovery from initial drug effects. Treatment with bortezomib, cisplatin, eribulin, paclitaxel or vincristine induced a dose-dependent loss of neurite/process areas, mimicking the 'dying back' degeneration of axons, a histopathological hallmark of clinical CIPN in vivo . The IC50 for neurite loss was within 3-fold of the maximal clinical exposure (Cmax) for all five CIPN-inducing drugs, but was >4- or ≥ 28-fold of the Cmax for 2 non-CIPN-inducing agents. Compound-specific effects, eg, neurite fragmentation by cisplatin or bortezomib and enlarged neuronal cell bodies by paclitaxel, were also observed. Collectively, these results support the use of a quantitative, morphologic evaluation and a DRG cell culture model to inform risk and examine mechanisms of CIPN.